The coordination effects of low-carbon city pilot and smart city pilot on urban land green use efficiency: evidence from a quasi-natural experiment in China - Li, Boya; Liu, Shuai; Song, Yuyu; Cui, Zehui (Frontiers in Earth Science, 2025)
Low-carbon city pilot and smart city pilot are two main measures which could improve urban land green use efficiency (ULGUE). In this study, we take two pilot policies as a quasi-natural experiment. Using the difference-in-differences (DID) method, we designate “dual-policy” cities as the treatment group to examine the combined effect of the policies on ULGUE. To our knowledge, this is the first attempt to integrate these two policies into a unified analytical framework. This framework allows us to investigate both their coordination effects and the magnitude of differences between dual and single policies. We find that (1) both the low-carbon pilot and the smart city pilot can improve the ULGUE. (2) Dual-pilot cities show a stronger enhancement of ULGUE than the cities with a single policy. (3) The policy sequence demonstrates varying effect magnitudes, suggesting that ecological regulation provides a solid foundation for subsequent technological upgrading.